The Baldrige Criteria for Educational Institutions - USA : Improvement Guide. - Tuominen, Kari. (Excellence Frameworks - Baldrige Series, 2013)
The book makes it easier to involve the entire staff of the educational institute in launching development.Excellent educational institutions assess their own operations regularly and use this information to predict demands in their operating environment. This forms the basis for the self-assessment and self- improvement in this manual.Using the Business Excellence Framework, it provides a series of 32 questions and contrasting pairs of examples specifically for educational facilities to help evaluate their performance highlighting areas that need adoption or those that are currently excelling.The book and the Excellence Framework applied will help you to identify the need and readiness for change by comparing your own practices with those of successful organizations.